The legal regime of urban planning in the spanish state: a global look - Fuentes i Gasó, Josep Ramon (2022)
This paper focuses on the study of urban planning and its legal regime in Spain. To do so, we begin with a brief reference to the urban and land use planning legislation in this country. Next, we deal with the legal nature of urban plans, and we mention the different types of planning: the general plan and its substitutes, sectorization, partial and special plans, detailed studies and other complementary instruments. Subsequently, we analyze the problems presented by the procedures of approval and alteration of urban plans, and finally, we refer to the situation of “out of order”, derived from changes in urban planning.